Scientometrics Study of Impact of Journal Indexing on the Growth of Scientific Productions of Iran. - Abbas Najari (Iranian Journal of Public Health, 2013)
This study represents scientific production of Iran in medical sciences field at recent years, and the correlation between scientific productions with the number of indexed journals.Data extracted from SCOPUS database between years 2000 and 2011, and Iran's performance measured in terms of different Scientometrics indexes including self-citations, percent of cited articles, number of articles with international collaboration and contribution of Iran in medical sciences in Middle East and world. Moreover correlation between the number of articles, citations, self-citations, and H-index and number of indexed journals for 50 countries in all fields is included.In 2011 year, Iran contributed 32.77 percent of the Middle East, and accounted for 1.57 percent of the world scientific production. The most frequent document type was original journal article published in English. Retrieved records revealed preferred subject areas, including medicine miscellaneous (14.53 percent of Iran publications in 2011 year). In 2011, according to the number of articles and citations to them, Iran was at 17th and 23th position between 226 countries, respectively. After adjustment for 19708 journals from 50 countries, Iran's rank based on the number of journals in medical sciences was 24th.The number of indexed journals with number of articles, citations, self-citations, and H-index of each country showed significant correlation (P-value